The Bank for International Settlements; an experiment in central bank cooperation - Schloss, Henry Hans (Amsterdam : North-Holland Pub. Co., 1958)
The bulk of this book is taken up by a review of the origins of the Bank for International Settlements; its structure and mechanical functions; its short-lived operations in facilitating the payment of reparations under the Young Plan; its modest contributions toward mitigating the financial crises of the early 'thirties; and the embarrassing position of the Bank during the second world war when, attempting to carry on its routine duties in a divided Europe, it incurred charges of collaboration with Germany.
"Based on the author's doctoral dissertation at Columbia University."
Includes index
"Bibliography": p. 170-176.
usc 18/05/18
Loans
Keywords: Bank for International Settlements